Organizational Resilience, Dynamic Leadership, Responsible Management and the Impact of VUCA: A Theoretical Framework - Khan, Rehmat Ullah; Afridi, Sajjad (South Asian Review of Business and Administrative Studies (SABAS), 2023)
The evolving domain of Responsible Management (RM) generally accentuates upon the combination of sustainability, responsibility, and ethics in managerial practices. Whereas modern managerial practices are comprehended as a fine amalgam of diverse elements including human capital and acumen, complex machineries and materials, methodological processes and practices. However, the impact created by abrupt economic dynamics, changing social needs, time-sensitive informational factors and in-time decision making in relation to corresponding environment characterized by volatility, uncertainty, complexity & ambiguity (VUCA) cannot be kept aside. Hitherto, the emerging trend identified in the recent past reveals that everything around us seems to be in a state of continuous flux. We are entombed in the vortex of an unending cyclone of change. Therefore, there is a dire need to understand the role of dynamic leadership in volatility, uncertainty, complexity and ambiguity inherent in the environment we are dwelling in, to analyze the challenges offered by them and to finally explore the solutions to overcome these challenges in the realm of Responsible Management (Singh & Sharma, 2022). Present study seeks to fill in this gap, using qualitative methodology, by offering a theoretically grounded framework to integrate organizational resilience, dynamic leadership and responsible management.